2016
DOI: 10.7287/peerj.preprints.1797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geography and location are the primary drivers of office microbiome composition

Abstract: North Americans spend the majority of their time indoors where they are exposed to the microbiome of the built environment (BE) they inhabit. Despite the ubiquity of microbes in BEs, and their potential impacts on health and building materials, basic questions about the microbiology of these environments remain unanswered. We present a study on the impacts of geography, material type, human interaction, location in a room, seasonal variation, and indoor and microenvironmental parameters on bacterial communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 15 publications
(15 reference statements)
2
35
0
Order By: Relevance
“…Correlation between OTU richness and RH was not observed in the autumn in any location, and temperature was not significantly correlated with OTU richness, regardless of season, and location (Spearman's correlation between each location and RH and temperature P < .05). The effects of temperature and RH on the indoor microbiome may be dependent on the BEs in question, as there have been mixed findings regarding the roles of these environmental conditions on indoor air or surface microbial assemblages …”
Section: Resultsmentioning
confidence: 99%
“…Correlation between OTU richness and RH was not observed in the autumn in any location, and temperature was not significantly correlated with OTU richness, regardless of season, and location (Spearman's correlation between each location and RH and temperature P < .05). The effects of temperature and RH on the indoor microbiome may be dependent on the BEs in question, as there have been mixed findings regarding the roles of these environmental conditions on indoor air or surface microbial assemblages …”
Section: Resultsmentioning
confidence: 99%
“…For example, recently in a study focused on bacterial biodiversity using the 16S locus, it was shown that a run effect can be confounded with a sample effect if it is not accounted for (e.g., by splitting sample groups across multiple Illumina runs, Chase et al, 2016); however, it remains to be seen whether such technical artefacts are also prevalent for loci used for metabarcoding plant and animals from eDNA (COI, 18S, ITS, etc. ), and more research is needed.…”
Section: Abundance Filteringmentioning
confidence: 99%
“…To illustrate the method, we apply it to two microbiome datasets. The first is a study of environmental microbiomes collected in office environments available from Qiita (http://qiita.microbio.me, Study ID: 10423). The samples are restricted to dust collected at university campuses in Toronto, Ontario, Canada and Flagstaff, Arizona, USA with at least 5000 classified reads, resulting in 981 samples.…”
Section: Applicationmentioning
confidence: 99%
“…The results for the dust data, collected by Chase et al Inference is performed on order, family, genus, and species levels. Univariate methods use the aggregates at each taxonomic level, whereas the distance methods use each component separately in the distance calculation.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation